“And all this is spoken of the naturall byrth . . .”: Metadiscourse in The Birth of Mankind and its German source text, Rosengarten - Whitt, Richard J. (John Benjamins Publishing, 2018)
This paper provides an examination of the use of metadiscourse in the two versions of The Birth of Mankind, the first midwifery manual to be printed in English during the sixteenth century. It is a translation of a Latin text, which itself is a translation of the German Rosengarten. While much has been made of the differences in the use of medical terminology in various versions, little attention has been paid to what differences – if any – exist in the ways the various authors/translators signal text structure or use other overt markers to the reader as to how the text is to be read or understood. Corpus linguistic methods are employed to provide a quantitative angle on the analysis of these texts.